Understanding discrimination in hiring apprentices : how training companies use ethnicity to avoid organisational trouble - Imdorf, Christian [Verfasser] (My University, 2017)
"Children of immigrants from non-EU countries face particular problems to access apprenticeship training in German-speaking countries. In this context this article asks how recruiters in small and medium sized companies (SME) make sense of national and ethnic origin when hiring new apprentices. The author proposes Boltanski and Thévenot’s theory of justification in order to conceptualise ethnic discrimination in hiring. Accordingly, the social body of a company consists of multiple interweaved (industrial, domestic, market) 'worlds' of social coordination and justification. In order to avoid organisational trouble and to guarantee the further existence of the company, these worlds claim different principle of personnel assessment, some of them penalising applicants of specific ethnic origin. Empirically, the article refers to apprentice recruitment in Switzerland and Germany. It illustrates that employers in SME expect trouble in the domestic and in the market world of the company when hiring school leavers they perceive as foreigners. Hence, discriminatory categories such as ethnicity are used as symbolic and organisational resources for trouble avoidance in hiring apprentices." (Authors' abstract ; BIBB-Doku)
Keywords: G 1.3.1.1 Ausbildungsstellenmarkt; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; S 3.2 Unternehmen und Behörden; P 1.5 Migranten; Klein- und Mittelbetrieb; Ausbildungsplatz; Bewerberauswahl; Ausländischer Jugendlicher; Diskriminierung; Bundesrepublik Deutschland; Schweiz